Low Oxalate Diet for Prevention of Kidney Stone Disease: A Literature Review - Alhamdi, Mochammad Haikal; Alimah, Ghina Jilan (SCRIPTA SCORE Scientific Medical Journal, 2024)
Background: Nephrolithiasis is the most common illness affecting the urinary system. It affects 600,000 Americans annually and about 12% of the world's population. It caused by a concentration of crystals that exits the kidney and genitourinary system. Calcium stones, primarily composed of calcium phosphate or oxalate, are present in about 80% of patients with nephrolithiasis. Kidney stones can be avoided by controlling the production of oxalate stones through the low oxalate dietary sources and regulating other factors that affect oxalate absorption. Objectives: The purpose of this literature review is to explain how to maintain a low-oxalate diet and other factors, such as enzymes, oxalate precursors, and bacteria in the colon, affect urine oxalate excretion and help prevent the formation of kidney stones. Methods: A summary of this literature was compiled using data from numerous internet resources. Ten earlier research RCTs or observational studies with statistical analysis—that met a number of inclusion criteria were used to support the goals of this work. The journal is available for open access, its publication year is at least 2014. Discussion: Consuming more water, DASH, low calcium and salt diet, and a low-oxalate diet can all considerably reduce the excretion of oxalate. Conversely, a poor dietary pattern has been associated with an increased risk of kidney stones. Oral formulations ALLN-177, Oxabact, and OxDC are helpful in lowering urinary oxalate levels. Conclusion: Kidney stone disease may be avoided by adopting a low-oxalate and low-precursor diet. Latar Belakang: Nefrolitiasis merupakan penyakit yang banyak terjadi pada sistem saluran kemih. Penyakit ini mempengaruhi 600.000 orang Amerika setiap tahunnya dan sekitar 12% populasi dunia. Hal ini disebabkan oleh peningkatan konsentrasi kristal di sistem genitourinari.  Pada pasien nefrolitiasis, 80% diantaranya disebabkan oleh pembentukan batu kalsium, terutama fosfat atau oksalat. Nefrolitiasis dapat dihindari dengan mengendalikan produksi batu oksalat melalui sumber makanan rendah oksalat dan mengatur faktor lain yang mempengaruhi penyerapan oksalat.Tujuan: Penulisan literatur ditujukan untuk mengetahui pengaturan pola makan rendah oksalat dan faktor lain seperti enzim, prekursor oksalat dan bakteri di usus sebagai pencegahan pembentukan batu oksalat di ginjal dengan menurunkan eksresi oksalat dalam urin. Metode: Literature review dilakukan dengan mengumpulkan berbagai literatur bersumber dari Internet. Digunakan 10 penelitian yang sesuai dengan kriteria inklusi, penelitian RCT ataupun studi observasional, artikel memiliki akses gratis, tahun terbit minimal 2014 Diskusi: Peningkatan konsumsi air, DASH, diet rendah kalsium dan rendah garam dapat menurunkan eksresi oksalat. Pola diet yang buruk dapat meningkatkan risiko pembentukan batu ginjal. Konsumsi ALLN-177, Oxabact dan OxDC membantu menurunkan oksalat urin. Kesimpulan: Pembentukan batu ginjal dapat dihindari dengan menerapkan pola makan rendah oksalat dan rendah prekursor oksalat.